The Impact of the Change in Discount Rate and Monetary Mass on the Economic Growth in Algeria, Standard Study for the Period 2000-2017 - laaraf, Faiza; bouguerra, rabeh (Journal of Research in Finance and Accounting, 2021)
discount rate, the monetary mass M2, and the economic growth rate in Algeria. measuring and knowing the nature and effect of the change in both the discount rate and the monetary mass M2 on the economic growth rate in Algeria for the period 2000-2017. This done by building a multiple regression model with the values ​​of the study variables. One of the most prominent results we obtained in this study was that there is a quasi-stability in the discount rate imposed by the Bank of Algeria on banks operating in Algeria, at rates of 4% and 3.5% during the period 2000-2017, and a general trend towards an increase and an expansion in the monetary mass M2 during the years 2000-2017. While we noticed a fluctuation in the rate of economic growth between slowdown and slight increase during the period 2000-2017. The standard results of the study found a correlation and an adverse and negative statistically significant effect of the discount rate and the monetary mass M2 on the economic growth rate in Algeria During the period 2000-2017.